Spatial and temporal variations of grassland vegetation on the Mongolian Plateau and its response to climate change - Li, Guangshuai; Yu, Lingxue; Liu, Tingxiang; Bao, Yulong; Yu, Jiaxin; Xin, Bingxia; Bao, Lun; Li, Xuan; Chang, Xinyue; Zhang, Shuwen (Frontiers in Ecology and Evolution, 2023)
The Mongolian Plateau is an arid and semi-arid region, and its main vegetation type is grassland, which has a fragile ecosystem and is a sensitive area for global warming. Based on MODIS NDVI data, meteorological observations including air temperatures, and precipitation data from 2000 to 2018, this study examined the spatial and temporal variation characteristics of grassland vegetation on the Mongolian Plateau during the growing season and its reaction to climate change. The study's findings demonstrate that the growing season average NDVI of grassland vegetation on the plateau gradually increased from southwest to northeast during the growing season; the growing season average NDVI demonstrated a significant overall increase of 0.0023/a (p < 0.01) from 2000 to 2018, with an increase rate of 0.0030/a in Inner Mongolia and 0.0019/a in Mongolia; the area showing a significant increase in NDVI during the growing season accounted for 91.36% of the entire study area. In the grasslands of the plateau, precipitation increased significantly at a rate of 3.4834 mm/a and average air temperature decreased slightly at a rate of -0.0018 °C/a during the growing seasons of 2000–2018. Changes in precipitation and average air temperature of grassland vegetation varied by region as well, with Inner Mongolia experiencing higher precipitation increasing rates (4.8346 mm/a) and lower cooling rates (-0.0074 °C/a) than Mongolia (2.6090 mm/a and -0.0246 °C/a, respectively). On the Mongolian Plateau, the NDVI of grassland vegetation in the growing season showed a significant positive correlation with precipitation (0.5386) and a significant negative correlation with average air temperature (-0.3389), indicating that increased precipitation in combined with declined air temperature led to an increase in NDVI. This work is crucial to further understanding surface–atmosphere interactions in arid and semi-arid regions in the context of global climate change.